Transatlantic Connections : Whitman U.S., Whitman U.K. - Thomas, M. Wynn (Iowa Whitman series., 2009)
In this series of textual readings and cultural comparisons, M. Wynn Thomas explores Whitman's amazing ability to appeal across distances and centuries. The book's contrasting sections reflect the two locations studied: the first shows Whitman in his time and place, while the second repositions him within the cultures of England and Wales from the late 19th to the late 20th century. In the opening chapter he is placed against the vivid, outrageous background of the New York of his time; the second finds evidence in his poetry of a critique of the new urban politics of the emerging city boss; t.